2021
DOI: 10.1021/acs.jafc.0c07046
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich Extract from Litchi chinensis Seeds Alleviates Hypertension-Induced Renal Damage in Rats

Abstract: Litchi chinensis seed is a valuable byproduct of the subtropical fruit litchi (L. chinensis Sonn.), whose extract (LSE) has been confirmed to ameliorate dyslipidemia, hyperglycemia, and oxidative stress caused by type 2 diabetes. However, if LSE exerts an effect on anti-hypertension and hypertensive renal damage remains unknown. In this study, 13 polyphenols and one fatty acid were identified by UPLC-Q/TOF-MS. Network pharmacological analysis revealed that the therapeutic effects of LSE may be involved in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The LSD (least significant difference) test was used for post hoc test. p < .05 was considered to be statistically significant 31 …”
Section: Methodsmentioning
confidence: 99%
“…The LSD (least significant difference) test was used for post hoc test. p < .05 was considered to be statistically significant 31 …”
Section: Methodsmentioning
confidence: 99%
“…In vivo, 10‐week treatment (60 mg/kg bw, p.o.) of the fruit seed's polyphenol‐rich extract reduced systolic blood pressure and serum endothelin 1 in spontaneously hypertensive rats (Yao et al., 2021). In fact, the blood pressure‐lowering effect of the extract was comparable to that of a 40 mg/kg bw valsartan (Yao et al., 2021), suggesting that litchi seed has a strong potential to reduce vasoconstriction and hypertension.…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 99%
“…of the fruit seed's polyphenol‐rich extract reduced systolic blood pressure and serum endothelin 1 in spontaneously hypertensive rats (Yao et al., 2021). In fact, the blood pressure‐lowering effect of the extract was comparable to that of a 40 mg/kg bw valsartan (Yao et al., 2021), suggesting that litchi seed has a strong potential to reduce vasoconstriction and hypertension. Chromatographic analysis showed that the extracts were rich in gallic acid and flavonoids, such as procyanidins, quercetin, rutin, catechin, and epicatechin (Kessy et al., 2018; Yao et al., 2021), which have been reported to exhibit inhibitory action on angiotensin I‐converting enzyme (Actis‐Goretta et al., 2003; Häckl et al., 2002; Jin et al., 2017; Oyagbemi et al., 2020; Takagaki & Nanjo, 2015).…”
Section: Pharmacological Phytochemical and Toxicological Aspects Of Litchi Fruit Seed And Peelmentioning
confidence: 99%
See 2 more Smart Citations